The Influence of Generations On Career Choice (Social Cognitive Career Theory Perspective) - Galuh Prawitasari (1st ASEAN School Counselor Conference on Innovation and Creativity in Counseling)
The aim of this study is to investigate the influence of generations on career choice based on Social Cognitive Career Theory (SCCT). Our literature studies conclude that individual’s career choice will be highly related to the major characteristics and values from his generation. Individual from the Traditional Generations will tend to choose careers which provide firm loyalty as his personal accomplishment, whether individual from Baby Boomers will tend to choose careers which provide prestiges, facilities, and positions. The X Generation lay their personal accomplishments on freedom and balance between career and family. Y Generation which known as digital natives tend to choose careers which give them freedom and creativity to work by utilizing high technology. Similiar to their former, the Z Generation not only tend to choose careers which give them freedom and creativity but also expect feedback from the experienced people.